(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2025)
This study aimed to explore the practical challenges of urban engineering design, particularly on the experiences of individuals with disabilities living in Naâma Province, Algeria. The study comprised a sample of 80 participants with disabilities, and it used a descriptive-analytical approach, employing a questionnaire as the primary data collection method.The study’s findings highlighted the prevalence of challenges faced by individuals with disabilities in Naâma Province, particularly within the domains of mobility and anthropometric considerations, internal spatial arrangements, and external environmental design, often and always indicating the presence of design-related issues. Keywords: Mobility Disabilities, Engineering Design.